Implementation of investment and working capital financing allocated by banks towards the added GDP, labors, and welfare in four regencies in Madura - Didin Fatihudin; Sjamsul Hidajat; Ma’ruf Sya’ban (Journal of Economics, Business, and Accountancy Ventura, 2015)
This study investigates the implementation of investment financing absorption and private bank sectors’ working capital to increase GDP, employment, and welfare of the four counties in Madura island (Bangkalan, Sampang, Pamekasan, Sumenep). This is the development of a previous study. This explanatory study is based on the model devel-opment concept or theory with Path Analysis through the data normality, multicolli-nearity, and heteroscedasticity test as well as causality. The data were taken from Bank Indonesia, Investment Coordinating Board, and the Central Bureau of Statistics. This is a time series data of 2002 to 2006. It shows that the financing of investment to GDP has significant and negative effect, financing of investment to labor absorption has signifi-cant and negative effect; financing working capital to GDP has significant and positive effect; financing of working capital to labor absorption has significant and negative effect; GDP in the labor market has no significant nor positive effect; GDP for the welfare effect, it has positive but not significant effect; employment in the welfare has a significant and positive effect. The direct effect or indirect implementation of financing from banks to finance investments and working capital to the entrepreneurs has increasingly a significant and positive effect. Absorption has dominated world finance working capital financing, following the least consumption and investment. Thus, it was natural that the implementa-tion of the investment credit and working capital has a significant and positive effect on economic growth, absorption of labor, and welfare in all four counties in Madura.